Leopardi e l'influenza pedagogica di Chesterfield. Annotazioni - Michele Zedda (Firenze University Press, 2022)
There is an eighteenth century collection of letters among sources of Leopardi's pedagogy. In March 1827 Leopardi reads Letters to His Son, composed by Lord Chesterfield, an English writer and politician, for his son Philip, in order to educate him to live in society and to make his own way in the world. This pedagogic lecture influences some of Leopardi's one hundred and eleven Pensieri. Also Leopardi's Pensieri is a practical pedagogic work, written to educate youth to savoir-vivre.